ARP2/3 complex mediates the neuropathology of PTEN-deficient human neural cells downstream of mTORC1 and mTORC2 hyperactivation - Navroop K. Dhaliwal; Octavia Yifang Weng; Ai Tian; Aditi Aggarwal; Mai Ahmed; Guoria Sun; Afrin Bhattacharya; Wendy W. Y. Choi; Haruka Nishimura; Pragnya Chakraborty; Xiaoxue Dong; Yuncheng Wu; et al. (Proceedings of the National Academy of Sciences, 2026)
Mutations in the phosphatase and tensin homolog ( PTEN ) gene are linked to severe neurodevelopmental disorders. Loss of PTEN causes hyperactivation of both mechanistic target of rapamycin (mTOR) complexes, mTORC1 and mTORC2. Recent studies have shown that this dual hyperactivation is required for the neuropathology observed in PTEN -deficient human stem cell–derived neural cells. However, the molecular effectors that integrate these synergistic signals remain unknown. Here, we identify the actin-regulating ARP2/3 complex as a critical point of convergence downstream of mTORC1 and mTORC2. We show that concurrent hyperactivation of both complexes drives increased filamentous actin and elevated levels of the ARP2/3 complex subunits in PTEN -deficient human neural precursors (NPs) and neurons. Pharmacological or genetic inhibition of ARP2/3 is sufficient to rescue multiple disease-relevant phenotypes, including NP hyperproliferation, neuronal hypertrophy, and electrical hyperactivity, without affecting the upstream mTORC1 or mTORC2 hyperactivation. Together, these findings reveal the PTEN –mTOR–ARP2/3 signaling axis as a core mechanism of neuropathology and highlight ARP2/3 inhibition as a potential therapeutic strategy for PTEN -related neurodevelopmental disorders.